PENGARUH PEMBERIAN INTERVENSI THORACIC SPINE MOBILITY EXERCISE TERHADAP POSTUR KYPHOSIS PADA PEREMPUAN BEKERJA - NUR ACHIRDA; Mohammad Ali; Resky Wiradhika (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Abstract Background: Kyphosis is a change in the position of the spine which causes the back surface to bend less than normal. Ideally, the spine has a curvature of about 20 to 29 degrees. However, kyphosis has a spinal curvature of >29 degrees or more. This is what makes Kyphosis sufferers have a bent body position. Research method belongs to the type of Pre-Experimental research with the One Group Pre Test and Post Test design. This study aims to determine the impact before and completion of the intervention aimed at the Effect of Intervention Thoracic Spine Mobility Exercise on Posture Kyphosis in Working Women with a sample of 35 people, in this study an intervention before (Pre-Test) and after (Post-Test) was given. treatment. Results of the results of the normality test with Shapiro-Wilk then obtained p value (> 0.05) in each group of data. The conclusion is normally distributed, the intervention in the form of Thoracic Spine Mobility Exercise has a significant difference because the p-value <0.05 is 0.003 Conclusion There is a significant effect on posture correction in Kyphosis patients after being given Thoracic Spine Mobility Exercise intervention.